Church and Youth Resilience to Substance Abuse: Assessing Church Responses, Challenges and Gaps - Chanda, Armstrong (Pascasarjana IAIN Pontianak, 2025)
Realising the fundamental role of the church in youth development and social work, the study investigates the responses, challenges and gaps in combating youth substance abuse by the church. It highlights the need for holistic interventions while emphasising the need for mental health resilience. The study employed a qualitative approach, combining document analysis and review of literary materials to assess church and substance abuse among youth, especially cases studied in the Philippines and Kenya. The findings indicate that the church’s interventions in youth substance abuse include moral teachings, awareness raising and support project activities. The study also underscores the importance of family dynamics in developing resilience against substance abuse. The major challenges faced by the church concerning youth substance abuse and promoting resilience include poverty and peer pressure, which hinder the youth’s desire to undergo interventions. Moreover, cultural stigma and denial from the parents or guardians block the youth from seeking help. Cultural belief systems also disrupt family connections, further underlining the need for robust support systems. An enormous gulf exists between the church and the youth, which undermines any preventative measures that might be undertaken. The research proffers useful pointers for policymakers, church leaders, and social workers regarding the lifestyle aspects that link faith, culture, and youth substance addiction. It recommends that the church customise its approaches to address the specific challenges faced by young people struggling with substance abuse, focusing on health, healing, and resilience, aligning with the challenges faced by different youths and the need for urgent attention.